THE ROLE OF LIQUIDITY MANAGEMENT IN DRIVING FINANCIAL PERFORMANCE: A STUDY OF PUNE’S JEWELLERY FIRMS - Bora, Suhas; Lakhangaonkar, Supriya (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The gems and jewellery business holds a key position in India’s economic framework, serving as a substantial contributor to exports, employment generation, and domestic consumption. This pilot study evaluates the financial performance attained through liquidity management strategies utilised by 60 prominent jewellers in Pune over the past 14 years. This research primarily observes changes in liquidity management. It applies the paired sample t-tests and correlation analysis to assess hypotheses on the impact of liquidity on profitability. The findings of the study clearly indicates that effective liquidity management has a favourable and significant effect on profitability. The findings offer important inputs for jewellery firms and financial planners, highlighting the significance of strong liquidity management to guarantee financial flexibility and profitability.